KAJIAN KEBERADAAN FORMALIN DAN BORAKS PADA IKAN ASIN DI NAGARI SASAK KABUPATEN PASAMAN BARAT - Yusra .; Sindy Gemaeka Putri; Lidya Dwi Handayani (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2023)
From several studies it was revealed that there are still many people who use formalin and borax in food because these ingredients are easy to obtain. Nagari Sasak is one of the areas in the Sasak Ranah Pasisia District, West Pasaman Regency, located on the coast where most of its residents produce salted fish for their livelihood. The procedure used by fishermen in this area when processing salted fish is still traditional. This study aims to analyze the presence of formalin and borax in salted fish processed by conventional fishermen in Nagari Sasak, Sasak Ranah Pasisia district, West Pasaman regency. The samples used in this study included seven types of dried salted fish obtained from three processors in KanagarianSasak. For more details, the types of salted fish tested consist of three kinds of anchovy (Stolephorus sp.), giant trevally (Caranx sp.), yellow jack (Caranx sp.), barracuda (Sphyraena jello), and tobi (Sardinella fimbriata). The research sample was obtained by purposive sampling way. In addition, the method used in this research is the descriptive method, while the data analysis is gained through qualitative descriptive methods. The test parameters of this study included formalin and borax qualitative tests and organoleptic tests of dried salted fish. The results showed that five out of seven salty fish samples, as much as 71.43%, were detected to contain formalin.